Hyperosmolar hyperglycemic syndrome: A comprehensive review of clinical presentation, diagnosis, and treatment strategies in hyperglycemic crises - Orłowska, Dominika; Kapłan, Wojciech; Ostański, Jan; Zalewa, Karolina; Bartoszek, Lidia; Świdziński, Rafał; Skorupski, Bartosz; Lipiec, Jakub; Rogowska, Monika; Olszak, Joanna (Journal of Education, Health and Sport, 2024)
Introduction and Purpose Hyperosmolar Hyperglycemic State (HHS), a severe type 2 diabetes complication, presents with profound hyperglycemia, hyperosmolality, and dehydration sans ketosis, posing distinct challenges in diagnosis and treatment compared to diabetic ketoacidosis (DKA). This article aims to enhance medical community awareness by examining HHS features, prevalence, and associated risk factors, contributing to improved clinical management. Emphasizing tailored treatment strategies for dehydration, coexisting illnesses, and metabolic decompensation, it ultimately seeks to enhance outcomes for type 2 diabetes individuals. Material and methods Conducting a systematic review of medical articles from 1972 to 2023 using PubMed, this study analyzed keywords such as hyperglycemic hyperosmolar state, HHS, diabetes mellitus, hyperglycemia, and dehydration. Inclusion of pertinent articles ensured a comprehensive exploration of Hyperosmolar Hyperglycemic State (HHS) literature during the specified timeframe. Brief description of the state of knowledge. Hyperosmolar Hyperglycemic Syndrome (HHS) predominantly affects elderly type 2 diabetes individuals, often triggered by infections like pneumonia or urinary tract infections. Clinical presentation includes fatigue, weakness, polydipsia, polyuria, nausea, and altered consciousness. Diagnosis relies on criteria such as elevated blood glucose levels and increased osmolality. HHS management involves a multidisciplinary approach, addressing fluid depletion, compromised cerebral perfusion, and achieving gradual normalization of osmolality and blood glucose levels to prevent complications. Summary Hyperosmolar Hyperglycemic Syndrome (HHS), a severe metabolic disorder linked to diabetes, extends beyond hyperglycemia, necessitating a comprehensive understanding. This review sheds light on HHS etiology, clinical manifestations, diagnostic criteria, and treatment modalities, emphasizing its critical nature in diabetes care.